2023
DOI: 10.3390/ma16062403
|View full text |Cite
|
Sign up to set email alerts
|

Enamel Evaluation after Debonding of Fixed Retention and Polishing Treatment with Three Different Methods

Abstract: Lack of standardization of the retention phase has led to many studies of stability of movements and characteristic of retainers, disregarding the enamel repercussions of fixed retention on this phase. This study aimed to analyze different methods of enamel polishing after detachment of orthodontic retainers. Forty-five healthy premolars were divided into three groups according to the polishing bur after debonding, and four specimens without intervention were used as control. A 0.038 × 0.015 inches gold chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Our findings are also consistent with those of Iglesias et al, who reported improved enamel preservation after polishing with the tungsten carbide bur at a low speed [34].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are also consistent with those of Iglesias et al, who reported improved enamel preservation after polishing with the tungsten carbide bur at a low speed [34].…”
Section: Discussionsupporting
confidence: 93%
“…Some authors have used profilometry to measure the depth of the grooves [17,27,28], while others have compared digital models using three-dimensional scanners to observe changes in the anatomy or measure the depth of cracks and grooves [30][31][32]. In turn, other studies have made use of atomic force microscopy (AFM) [22,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The spontaneous repair of enamel microcracks is a common phenomenon in live teeth, safeguarding against crack propagation to the dentin and dental pulp, and this reparative process was also observed in extracted teeth, as mentioned in the studies [57][58][59][60][61][62][63][64][65][66][67][68].…”
Section: Microcracksmentioning
confidence: 89%
“…For the purpose of maintaining long-term teeth alignment, the binding strength between the tooth and the composite pad, as well as the retention wire, was deemed optimal. Given that each approach examined increased the SR of the treated enamel, further research into remineralization processes is warranted [61].…”
Section: Surface Roughnessmentioning
confidence: 99%